MODELING THE FACTORS DETERMINING THE STATUS OF ECONOMIC DEVELOPMENT IN GANGA AND YAMUNA VALLEY OF UTTARKASHI DISTRICT, UTTARAKHAND: A TISM APPROACH - Gautam, Shyamlal; Singh, Virendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper presents a comprehensive model for analyzing the factors determining the status of economic development in the Ganga and Yamuna valleys of Uttarkashi district, Uttarakhand, using the Total Interpretive Structural Modeling (TISM) approach. The region is characterized by a diverse economic landscape shaped by its geographical, cultural, and environmental context. Through extensive literature review and stakeholder consultations, this study identifies key factors influencing economic development, including agricultural productivity, tourism potential, infrastructure development, environmental sustainability, education and skill development, water resource management, government policies, migration trends, hydropower potential, and cultural heritage. Employing TISM, the paper systematically maps the relationships and hierarchies among these factors, revealing their interdependencies and identifying primary drivers of economic development. The findings highlight the importance of a holistic approach to policy formulation, emphasizing the need for integrated strategies that address the complexities of the local socio-economic environment. By providing a structured framework for understanding the dynamics of economic development in Uttarkashi, this research contributes valuable insights for policymakers, practitioners, and researchers dedicated to fostering sustainable growth in the region. The model not only aids in visualizing the interconnections between various factors but also serves as a decision-making tool for prioritizing interventions and resource allocation.